Recursos e capacidades estratégicos utilizados por empresas de confecção de vestuário de luxo - Vieira, Lais Duarte (2012)
This dissertation investigated the characterization of features and capabilities involved in business strategies more applicants in companies production of luxury, seeking competitive advantage, taking into account the perception of managers and customers of this type of product. The concepts used were related to resource-based view and strategy. Thus, the constructs were revised perceived value, competitive advantage, strategic management and strategic resources. The research method adopted was exploratory and descriptive, qualitative in nature, with interviews conducted based on a semi structured script. Were interviewed six managers of companies production of luxury and six consumers these companies. The content analysis technique was used for the treatment and interpretation of the data collected. As a result, it was possible to identify the resources strategic source of competitive advantage for companies studied, they are, the designer, the reputation of the brand name and innovation capacity of the designer. Through the model identified VRIO evidence points these resources as valuable, rare, difficult to imitate and dependent on the conditions organizational for use of your full potential. From the analysis of data collected was possible to see that the luxury product aims for perfection from the moment of conception and this requires that it be done with high aesthetic standard, is rare and inaccessible and conceived from innovative ideas.